Guardians of Health: Vaccines in the Battle Against Communicable Diseases Vaccination in Malaysia - Current Progress and Challenges - Ismail, Zulkifli; Balasundaram, Susheela; Megat Hashim, Megat Mohamad Amirul Amzar Bin (International Journal of Human and Health Sciences (IJHHS), 2025)
In humanitarian crises, vulnerable populations—such as refugees, displaced individuals, and those affected by conflict or natural disasters—face heightened risks of infectious disease outbreaks due to poor living conditions and limited access to healthcare. Vaccines play a crucial role in preventing the spread of diseases like measles, cholera, and polio, saving countless lives in these challenging settings. However, logistical challenges, vaccine hesitancy, and insufficient healthcare infrastructure often impede vaccination efforts. This presentation explores the critical role of vaccines in humanitarian contexts, highlighting some successes like measles control in Rohingya camps in Bangladesh, while examining the role of international organizations and innovations to overcome barriers. There is a need to continue efforts in preparedness, investments in strengthening healthcare systems and global cooperation to protect the most vulnerable population in a humanitarian crisis. International Journal of Human and Health Sciences Supplementary Issue 01: 2025 Page: S21